2011
DOI: 10.1097/iop.0b013e3181efa695
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience Using a New Modified Bone Nibbler for Superior Osteotomy During Endonasal Dacryocystorhinostomy

Abstract: We report the use of a new modified bone nibbler for removal of superior bone, even as high as the nasal roof, which previously in our practice could be removed only with PI. It allows a large osteotomy comparable to that achieved with powered endoscopic dacryocystorhinostomy yet avoids the disposable costs of PI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Another advantage that this technique of the osteotome and mallet has over powered instruments is the tactile feedback and resistance present when using the ostetome, which may prevent excessive destruction that can occur with powered instruments. We do not have any experience with the new bone nibbler as described by Patel et al 16 In the previous study by Cokkeser et al 17 it was reported that the procedure could be completed within 15 minutes. Given the fact that the duration of our operation went down to 22 minutes after just 9 initial operations, it is likely that with greater familiarity, shorter operation times can be achieved.…”
Section: Discussionmentioning
confidence: 84%
“…Another advantage that this technique of the osteotome and mallet has over powered instruments is the tactile feedback and resistance present when using the ostetome, which may prevent excessive destruction that can occur with powered instruments. We do not have any experience with the new bone nibbler as described by Patel et al 16 In the previous study by Cokkeser et al 17 it was reported that the procedure could be completed within 15 minutes. Given the fact that the duration of our operation went down to 22 minutes after just 9 initial operations, it is likely that with greater familiarity, shorter operation times can be achieved.…”
Section: Discussionmentioning
confidence: 84%
“…Thus a large osteotomy can be created that fully exposes the lacrimal sac, from its fundus down to the nasolacrimal duct junction and the agger nasi air cells posterior to the sac. 9 This allows the lacrimal sac to be fully marsupialised and flaps opened flat, both anteriorly and posteriorly, using a standard crescent blade.…”
Section: Methodsmentioning
confidence: 99%
“…Nasal endoscopy was normal apart from a narrow left nasal passage and deviated septum. The patient was recommended for left powered endonasal (DCR) 4 with septoplasty and intubation.…”
Section: Case Reportmentioning
confidence: 99%